Application and challenges of artificial intelligence in public health strategy optimization - Hui FA; Wenlie WU (Zhongguo gonggong weisheng)
Artificial intelligence (AI) has become a driving force for innovation in public health systems, significantly enhancing the efficiency and accuracy of public health services, particularly in disease risk monitoring, diagnosis, and treatment. However, the integration of AI with public health strategies is still in its early stages and faces numerous challenges. Continuous examination of potential problems and risks is crucial to ensure that the application of AI in public health is both safe and meets practical needs. This article provides an overview of the current state of AI in improving the efficiency of public health services, enhancing disease surveillance and response capabilities, and promoting health equity in the public health field. It also highlights the challenges faced by AI in data collection, algorithm accuracy, ethics, and privacy. This review aims to provide a reference for optimizing and enhancing public health strategies through the application of AI.